LICENSING POLICIES FOR YOUNG DRIVERS IN THE UNITED STATES - Williams, Allan F. (Assurances, 1997)
Although there is substantial variation in licensing policies in the United States, most states offer easy licensing at an early age. These policies have been associated with very high crash rates for young people, particularly 16 and 17-year-olds. A major shift in licensing regulations is now underway, with graduated licensing systems beginning to be introduced. In graduated licensing, on-road driving is encouraged but in lower-risk sitations before full privileges are granted. ln 1996, several states enacted graduated licensing provisions, and more are expected to do so in 1997. Provisions of graduated licencing such as night driving curfews for initial licence holders are the subject of considerable debate, as states struggle with setting the appropriate balance between mobility for young people and safety. Parents of teenagers are among the strongest supporters of graduated licensing.